2 - Analyse de la diversification des recettes fiscales en Afrique: des implications pour les politiques publiques - Bayale, Nimonka; Arnold Yao, Jacques-Patrick (Africa Development, 2024)
Recent economic shocks, including the COVID-19 pandemic, illustrated the fragility of public policies built around concentrated revenue sources. The need for a more diversified tax structure is an important concern in developing countries. This article analyses the Tax Revenues Diversification (TRD) in 39 African countries over the period 2005-2019, distinguishing between resource-rich and resource-poor countries. An index for monitoring TRD is constructed. The results indicate that the average value of this index in Africa is 0.846, reflecting weak performance in terms of TRD. Moreover, factors that determine TRD are analyzed using the Bayesian Model Averaging (BMA) approach, the Generalized Moment Method (GMM) and the Least Squares Dummy Variable Corrected (LSDVC). The results show that economic development and diversification, promotion of the industrial sector, trade, education, and financial development and digitalization enhance TRD, whereas informal economy, natural resources, corruption, and political instability inhibit TRD. Thus, the government policies should focus on economic diversification, digitalization development, gradual taxation of the informal sector, and improving the quality of institutions to diversify and increase tax revenue mobilization.